DRESS Syndrome in the ICU: When a Patient Is Treated with Multiple Drugs. (24th January 2016) - Moriceau, Florent; Prothet, Johanne; Blaise, Benjamin J.; Ben Said, Benoit; Page, Mathieu; Ber, Charles-Eric; Crozon, Jullien; Rimmelé, Thomas
Abstract : The Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome is life-threatening. It associates a skin condition with hematological and visceral disorders. The DRESS syndrome diagnosis in the intensive care unit (ICU) is difficult as clinical features are nonspecific. Furthermore, the need to treat patients with multiple drugs usually prevents the identification of the causative drug. We report the case of a patient who developed two bouts of DRESS caused by piperacillin-tazobactam, the first being complicated with a distributive shock. Cases of DRESS occurring inside ICU are seldom reported. However, any intensivist may encounter this situation during his career and should be aware of its diagnostic and management specific aspects.